Experimental Investigation of Delta Phase Precipitation in Inconel 625 Superalloy Aged at 550, 625 and 725 degrees C - Baldan, Renato [UNESP]; Araujo Pinto da Silva, Antonio Augusto; Tonno, Tiemi Manfia [UNESP]; Costa, Eliara Torres da; Negri Brentegani, Joao Tictor; Couto, Antonio Augusto (Univ Fed Sao Carlos, Dept Engenharia Materials, 2020)
The delta is an important stable phase that replaces the metastable gamma '' in the microstructure of Inconel 625 superalloy. The present work aims to investigate the kinetic of delta-phase precipitation in the microstructure of Inconel 625 nickel-based superalloy aged at 550, 625 and 725 degrees C up to 1000 h. Aging temperatures were chosen based on the thermodynamic simulation using JMatPro software which indicated that this phase is stable at temperatures below 905 degrees C. Microstructure of the heat-treated samples was analyzed via SEM/EDS and microhardness evolution was perfonned by Vickers microhardness tests. The results have shown that the samples aged at 550 degrees C (all times), 625 degrees C (all times) and 725 degrees C up to 200 h did not presented microstructural evidences of delta precipitation. However, samples aged at 725 degrees C for 500 and 1000 h clearly presented an acicular delta-phase precipitated mainly at the grain boundaries. It was noted changes in the microhardness at different aging time and temperatures probably due to the presence of gamma '' and/or delta phases. The sample aged at 625 degrees C for 1000 h presented the highest microhardness value (333 +/- 10 HV).
Keywords: Inconel 625; delta phase; aging; microstructure; superalloy